Fatores de risco no patrulhamento da GNR em ambiente operacional - Contente, Felisberto Português (2016)
In the mid-twentieth century, Portugal took the first big step towards social awareness of the Safety and Health at Work. Still later, the International Labour Organization and the World Health Organization were responsible for setting global guidelines that clarified the States for the way forward in inguito of safeguarding the common interests of workers, businesses and the state. All workers should be covered by the rules governing matters relating to Safety, imperative requirements established in the Constitution of the Portuguese Republic. These also include those soldiers from National Guard who, in contemporary social conjecture face in their everyday life situations worthy of heightened risk aquidade. Ensure the identification of risk factors to which they are exposed, is, first, a big boost in the way of preserving the safety of these employees, who daily selflessly and under the most adverse working conditions fulfill the mission of the Guarda Nacional Republicana. Adverse weather conditions, and violence at work are two examples of risk factors to which the military Guard are daily exposed, and hence arise many days of absence from the workplace. The purpose of this study is to identify the main risk factors to which the military from GNR are exposed during dismounted patrols, and also provide solutions on ways to mitigate and manage the risks presented. The cognitive distance traveled, throughout this study led us to demonstrate that it has been done by the GNR chain of Command, a huge effort to ensure through various forms (including emphasize the new Regulation of Uniforms), the resolution of the main factors that may jeopardize the integrity of the patrolmen, betting this Institution in the protection of the military that compose it, and the prevention of accidents at work through training and systematic monitoring that superiors expend with its employees.